Primary Students' Experiences of Remote Learning during COVID-19 School Closures: A Case Study of Finland - Anni Loukomies; Kalle Juuti (MDPI AG, 2021)
The remote learning period that took place due to the outbreak of the COVID-19 pandemic in the spring of 2020 was a novel experience for many students, teachers and guardians in Finland and globally. To be prepared for similar occasions in the future and to support all students appropriately, it is important to be aware of students' experiences. In this study, instant video blogging (IVB) was used to collect primary school students' first-hand reports of their emotions in remote learning situations. Through an experience sampling method, 23 Finnish fifth-grade students (aged 11-12 years) took part in IVB during the remote learning period 18 March 2020-13 May 2020. Students' expressions related to negative emotional experiences were more diverse than those related to positive ones. Nice was the most often reported positive evaluation related to studying. The most often reported negative feelings were bored and irritated, and the most often reported negative aspects related to learning were difficult tasks or not having learned anything. Towards the end of the research period, positive mentions about returning to school increased. The IVB method offered direct insight into how primary students experienced the remote learning period, which can support preparation for exceptional periods in the future and the development of digital learning solutions.